Alien invasion : how the Harris Tories mismanaged Ontario - Cohen, Ruth (Insomniac Press, 2001)
Alien Invasion is the first critical look at the past eight years of Tory rule in Ontario. How did a province renowned for being middle-of-the-road suddenly embrace the forces of far-right conservatism? How have the cuts to health care, the spectre of private universities, regular public sector strikes, and the tragedy in Walkerton all come to pass? Here, 20 essays expose strategies the Harris government has previously hidden from view. Using criticism, commentary and transcripts of government seminars, Alien Invasion reveals the techniques that a group of ''whiz kids'' working for the Harris.